2017
DOI: 10.3389/fnhum.2017.00476
|View full text |Cite
|
Sign up to set email alerts
|

Language Learning Variability within the Dorsal and Ventral Streams as a Cue for Compensatory Mechanisms in Aphasia Recovery

Abstract: Dorsal and ventral pathways connecting perisylvian language areas have been shown to be functionally and anatomically segregated. Whereas the dorsal pathway integrates the sensory-motor information required for verbal repetition, the ventral pathway has classically been associated with semantic processes. The great individual differences characterizing language learning through life partly correlate with brain structure and function within these dorsal and ventral language networks. Variability and plasticity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Tentatively, this could indicate that inverted words were accessed directly as full lexical units, as suggested above, although further research would be needed to test this conjecture. Alternatively, note that the ventral route can afford compensatory mechanisms when the dorsal stream is overloaded 22 , not developed, or dysfunctional [23][24][25][26] . Therefore, the distinctive diffusion pattern found in the UF and ILF may be linked to the systematic recruitment of supporting ventral mechanisms upon excessive demands placed on dorsal routes by continual practice of backward speech.…”
Section: Discussionmentioning
confidence: 99%
“…Tentatively, this could indicate that inverted words were accessed directly as full lexical units, as suggested above, although further research would be needed to test this conjecture. Alternatively, note that the ventral route can afford compensatory mechanisms when the dorsal stream is overloaded 22 , not developed, or dysfunctional [23][24][25][26] . Therefore, the distinctive diffusion pattern found in the UF and ILF may be linked to the systematic recruitment of supporting ventral mechanisms upon excessive demands placed on dorsal routes by continual practice of backward speech.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, TBAA was used to register diffusion-weighted images of all study participants to a standard template (Hsu et al, 2015), in which tractograms of 76 major WM tracts were developed using deterministic tractography. Lopez-Barroso and De Diego-Balaguer, 2017); there were 14 tract bundles on language network by our definition, so the LN brain age metrics were estimated using 14 GFA and 14 MD values. Table 5 provides the constitution of the language network in WM.…”
Section: Tract-based Analysis For Diffusion-weighted Imagesmentioning
confidence: 99%
“…When linking behavioral performance with neural activities, neuroimaging studies have supported the frontotemporal system as the neural substrate of language function (Van Der Lely and Pinker, 2014;Chang et al, 2015;and Lopez-Barroso and De Diego-Balaguer, 2017;Campbell and Tyler, 2018). Other studies have extended the domain-specific language network (LN) to a domain-general system or multi-demand network including the frontoparietal connections (Duncan, 1995;Unsworth et al, 2014;Cole et al, 2015;Duncan et al, 2017) and observed an association between the age-related decline of the domain-general system or multi-demand network and that of executive functions such as inhibition, attention, and working memory (Duncan et al, 2017;Chen P.-Y.…”
Section: Introductionmentioning
confidence: 99%
“…Human language function plays a role in the left hemisphere [1]. Aphasia has indicated an language impairment effect in the production and/or comprehension of speech and is one of the common sequelae following stroke in the left hemisphere [2,3]. Aphasia was shown in approximately 21-38% of acute stroke patients, and the major damaged lesion is the left perisylvian [4].…”
Section: Introductionmentioning
confidence: 99%